The necessary and sufficient conditions for the integral of a multivalued map to be a polygon - Boussouar, Ahmed; Arino, Ovide; Gautier, S. (Zielona Góra: Uniwersytet Zielonogórski)
Let F be a multivalued map from I := [a, b] into IR2 defined by F(t) = {h(t), f(t)}, where f and h are continuous maps from I into IR2. The aim of this paper is to find the necessary and sufficient conditions on the mappings f and h for an integral of F to be a convex polygon.
Keywords: sterowanie; sterowanie-teoria; sztuczna inteligencja; matematyka stosowana; informatyka